2013
DOI: 10.1016/j.toxlet.2012.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene affects fatty acid oxidation in livers from ovariectomized rats by acting as a pro-oxidant agent

Abstract: Estrogen deficiency accelerates the development of several disorders including visceral obesity and hepatic steatosis. The predisposing factors can be exacerbated by drugs that affect hepatic lipid metabolism. The aim of the present work was to determine if raloxifene, a selective estrogen receptor modulator (SERM) used extensively by postmenopausal women, affects hepatic fatty acid oxidation pathways. Fatty acids oxidation was measured in the livers, mitochondria and peroxisomes of ovariectomized (OVX) rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Even though all the aforementioned alterations can occur in a healthy liver, it has also been reported that a pre‐existing fatty liver, or even only risk factors for this condition, may contribute to a higher incidence of advanced forms of fatty liver disease caused by certain drugs. An example is the development and worsening of the hepatic steatosis caused by the oestrogen receptor modulators tamoxifen and raloxifene, via impairment of both mitochondrial function and FFA β‐oxidation, as well as stimulation of the de novo FFA synthesis . In these cases, obesity and other metabolic risk factors have been identified as independent predictors …”
Section: Drugs As Pathogenic Factors In Fatty Liver Development and Pmentioning
confidence: 99%
“…Even though all the aforementioned alterations can occur in a healthy liver, it has also been reported that a pre‐existing fatty liver, or even only risk factors for this condition, may contribute to a higher incidence of advanced forms of fatty liver disease caused by certain drugs. An example is the development and worsening of the hepatic steatosis caused by the oestrogen receptor modulators tamoxifen and raloxifene, via impairment of both mitochondrial function and FFA β‐oxidation, as well as stimulation of the de novo FFA synthesis . In these cases, obesity and other metabolic risk factors have been identified as independent predictors …”
Section: Drugs As Pathogenic Factors In Fatty Liver Development and Pmentioning
confidence: 99%
“…In contrast, gonadectomized male rats fed a high fructose diet did not develop hypertension, suggesting that testosterone may act as a causal link between insulin resistance/hyperinsulinemia and hypertension, and it is the absence of testosterone that prevented the development of fructose-induced hypertension [49]. In general, physiological concentrations of estrogen have beneficial effects on lipoproteins, insulin, and glucose metabolism [50]. Estrogen can improve insulin action in the liver, muscle, and adipose tissue by increasing glycogen deposition, glucose uptake, and lipogenesis [51].…”
Section: Endothelial Dysfunction Aggravates Fructose-induced and Ua-imentioning
confidence: 99%
“…Interestingly, inhibition of mtFAO has been documented with several of these drugs, namely tamoxifen, raloxifene and NRTIs [3,28,93,94]. Moreover, drugs such as tamoxifen, methotrexate and NRTIs can inhibit MRC activity and favor oxidative stress [3,16,28,95,96].…”
Section: Drug-induced Inhibition Of Mtfao and Aggravation Of Nafldmentioning
confidence: 99%